Mitochondria and Lysosomes: Discovering Bonds - Todkar, Kiran; Ilamathi, Hema S.; Germain, Marc (Frontiers in Cell and Developmental Biology, 2017)
In the last decade, the traditional view of lysosomes has been challenged by the recognition that lysosomes are not only degradative organelles, but also metabolic sensors that play a key role in the regulation of metabolism and cell growth. Similarly, mitochondria are now seen as crucial metabolic hubs dictating cell fate decisions, not just ATP-producing machines. Importantly, these functions are generally performed as a coordinate response of distinct organelles that are physically and functionally connected. While the association between mitochondria and the endoplasmic reticulum is well known, a similar interaction between mitochondria and lysosomes is now emerging. This interaction could be required to shuttle amino acids, lipids and ions such as calcium between the two organelles, thereby modulating their metabolic functions. In addition, a tethering complex linking two organelles has recently been described in yeast, although the mammalian counterpart has yet to be identified. Here, we discuss the implications of these recent findings.